Osteosarcoma: Molecular Pathogenesis and iPSC Modeling. Issue 8 (August 2017) - Lin, Yu-Hsuan; Jewell, Brittany E.; Gingold, Julian; Lu, Linchao; Zhao, Ruiying; Wang, Lisa L.; Lee, Dung-Fang
Abstract : Rare hereditary disorders provide unequivocal evidence of the importance of genes in human disease pathogenesis. Familial syndromes that predispose to osteosarcomagenesis are invaluable in understanding the underlying genetics of this malignancy. Recently, patient-derived induced pluripotent stem cells (iPSCs) have been successfully utilized to model Li–Fraumeni syndrome (LFS)-associated bone malignancy, demonstrating that iPSCs can serve as an in vitro disease model to elucidate osteosarcoma etiology. We provide here an overview of osteosarcoma predisposition syndromes and review recently established iPSC disease models for these familial syndromes. Merging molecular information gathered from these models with the current knowledge of osteosarcoma biology will help us to gain a deeper understanding of the pathological mechanisms underlying osteosarcomagenesis and will potentially aid in the development of future patient therapies. Trends: Osteosarcoma can be derived from undifferentiated/dedifferentiated mesenchymal stem cells and osteoblast-committed cells with differentiation defects. Other than mutations, genomic rearrangements are also involved in osteosarcomagenesis, which may be ignored by traditional mutation analysis. Osteosarcoma-specific fusion genes offer potential therapeutic targets for further osteosarcoma treatment. Insights gained from osteosarcoma-prone diseases highlight numerous interesting concepts linked to cancer development, including differentiation control, tumor-associated immunosuppression, and autophagy. Several osteosarcoma-prone iPSC disease models have been established, including Li–Fraumeni syndrome, hereditary retinoblastoma, Werner syndrome, and Diamond–Blackfan anemia. These systems provide a new platform for modeling and investigating the pathogenesis of osteosarcoma.